The Role of Law in Encouraging Community Compliance to Pay Mall Zakat and Taxes - Mhd Syukur Sihombing; Asmuni; Isnaini Harahap (Faculty of Law, Universitas Pekalongan, 2024)
This study examines the role of law in encouraging community compliance with the payment of zakat and taxes, considering the importance of these two obligations for social welfare and state development. The research problem focuses on the low level of community compliance in fulfilling zakat and tax obligations in several regions. The purpose of this research is to understand how law, both Islamic law and state law, can contribute to increasing public awareness and compliance. The research method used is qualitative with a case study approach. The data was collected through in-depth interviews with various stakeholders, including religious leaders, tax officials, and the general public. In addition, analysis of related legal and policy documents is also carried out to gain a comprehensive understanding. The results of the study show that the law has a significant role in creating compliance. Legal education about zakat and tax obligations is very necessary to increase public understanding. The involvement of community leaders and scholars has proven to be effective in motivating the community to fulfill their obligations. Transparency in the management of zakat and taxes is also a key factor that increases public trust, thus encouraging them to be more compliant. This research provides recommendations to strengthen the legal framework and more intensive education programs, in order to create higher awareness among the public about the importance of zakat and taxes in social development.